Antimalarial and Antioxidant Activities of Isoprenylated Coumarins from the Stem Bark of Mesua borneensis L. - Mulyadi Tanjung (Taylor & Francis Online, 2016)
The aim of this study was to assess the antimalarial and antioxidant effects of the n-hexane and ethyl acetate extracts together with three isolated isoprenylated coumarins, mammea A/BA(1),mammea A/ AA cyclo D (2) and mesuol (3) from the stem bark of M. borneensis L. The n-hexane and ethyl acetate extracts, as well as compounds 1-3 were evaluated for their antimalarial activity against Plasmodium falciparum strain 3D7 (chloroquine-sensitive) and their antioxidant activity against DPPH radical scavenging. Compound 2 exhibited slightly more active than chloroquine. Compounds 1 and 3 showed very high activity against DPPH radical.